EVALUASI UJI DENSITY METODE ASTM D 1298 dan D 6822 - Arluky Novandy (Swara Patra, 2019)
Density of liquid testing is one of the important test to determine quality of fuels, especially for determining contamination of fuels. In the field, we found that many fuel distributors and transporter of fuel are implementing one of these two methods, namely ASTM D 1298 or ASTM D 6822. These two methods have different procedure, consequently, different precission and correction. In this article, the writer recommand that ASTM D1298 is more precize than others due to there is no meniscus correction for opaque liquid stated on ASTM D 6822.